Joshua Maponga"s interactions with Black theology, African identities and Indigenous belief systems - Mujinga, Martin (HTS teologiese studies, 2025)
The intersection of Black theology, African cultural identities and Indigenous belief systems has been topical in South Africa, given the apartheid history of the country. Black South Africans used theology to define their cultural identities and belief systems in their quest for liberation. The need to engage this symbiotic relationship in Zimbabwe arose with Joshua Maponga III, who used his theological background as a pastor to analyse the meaning of African cultural identities, Indigenous belief systems and the place of theology among suffering Africans. This article aims to interrogate Maponga’s writings, presentations and interviews on social media to find out how he drew from African cultural epistemologies to develop a Black theological perspective and define African cultural identities and Indigenous beliefs. The article argues that Maponga’s work offers a unique insight into how African culture can inform and enrich Black theological discourses. It discusses the methodology used and Maponga’s background. It further analyses how African cultural resources, such as traditional myths, rituals and symbols, enabled Maponga to develop a theology rooted in Black people’s experiences, challenging the dominant Western theological paradigms that have marginalised African culture and theological perspectives for years. Furthermore, the article discusses the implications of Maponga’s work for the ongoing development of Black and African Theologies. It concludes by stating that Maponga’s work offers an example of how African cultural resources can be used to develop a theology that is both contextual and liberative.Contribution: This study highlights the significance of intersectionality and contextualisation in theological research while also challenging dominant Western theological paradigms and emphasising the importance of African cultural epistemologies. It contributes to methodological innovation in theological research and provides implications for the ongoing development of Black and African Theologies.